ESR signals in quartz: Applications to provenance research – A review. (18th March 2016) - Toyoda, Shin; Nagashima, Kana; Yamamoto, Yuya
Abstract: The oxygen vacancies in quartz, measured by electron spin resonance (ESR) as the E 1 ′ center, and crystallinity index (CI) of quartz by X-ray diffraction have been found to be useful tracers for provenance of sediments. This paper will review the principles of the methods and summarize typical examples of the applications. The differences in sources of loess in Japan were found between MIS 1 and 2 by examining the numbers of the oxygen vacancies, measured as the E 1 ′ center. Together with CI, the contributions from the Taklimakan and Gobi deserts to marine sediments in Japan Sea were quantitatively investigated. The contribution from Taklimakan correlates with the warmer proxy for the period up to 150 ka. The temporal change in the numbers of oxygen vacancies in quartz of atmospheric depositions in two Japanese cities correlate with the frequencies of "Kosa events", while the temporal change in another city does not correlate but shows gradual decrease, indicating that the route of the transportation of aeolian dust would be different for locations within Japan. Impurity centers in quartz would also be useful indicators for provenance of river sediments, but the current results indicate that the mixture of the river sediments is not simple.